Foam Cells in Atherosclerosis: Novel Insights Into Its Origins, Consequences, and Molecular Mechanisms - Gui, Yuzhou; Zheng, Hongchao; Cao, Richard Y. (Frontiers in Cardiovascular Medicine, 2022)
Foam cells play a vital role in the initiation and development of atherosclerosis. This review aims to summarize the novel insights into the origins, consequences, and molecular mechanisms of foam cells in atherosclerotic plaques. Foam cells are originated from monocytes as well as from vascular smooth muscle cells (VSMC), stem/progenitor cells, and endothelium cells. Novel technologies including lineage tracing and single-cell RNA sequencing (scRNA-seq) have revolutionized our understanding of subtypes of monocyte- and VSMC-derived foam cells. By using scRNA-seq, three main clusters including resident-like, inflammatory, and triggering receptor expressed on myeloid cells-2 (Trem2hi) are identified as the major subtypes of monocyte-derived foam cells in atherosclerotic plaques. Foam cells undergo diverse pathways of programmed cell death including apoptosis, autophagy, necroptosis, and pyroptosis, contributing to the necrotic cores of atherosclerotic plaques. The formation of foam cells is affected by cholesterol uptake, efflux, and esterification. Novel mechanisms including nuclear receptors, non-coding RNAs, and gut microbiota have been discovered and investigated. Although the heterogeneity of monocytes and the complexity of non-coding RNAs make obstacles for targeting foam cells, further in-depth research and therapeutic exploration are needed for the better management of atherosclerosis.